THE IMPLEMENTATION OF GUIDED QUESTIONS TECHNIQUE IN IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Fadilah; Zuhra; Syam, Hijrah (Datokarama English Education Journal, 2022)
This research aims at finding out whether the implementation of guided questions technique can improve the students’ ability in writing descriptive text or not. The researcher applied a quasi-experimental research design which involved experimental class and control class. The population of this research was the second-grade students of SMP Negeri 1 Toribulu. The sample was VIII B as the control class and VIII C as the experimental class that consist of 20 students for each class. The researcher applied the purposive sampling technique. The instrument used to collect the data was test. The pre-test was administered to measure the students’ ability in writing descriptive text before the treatment and the post-test was to measure the students’ ability after the treatment. The data gathered from the test were analyzed statistically. The result of the data analysis shows that the hypothesis of the research was accepted regarding the analysis that the tcounted (2,076) was higher than the ttable (2,0042). The degree of freedom (df) of the table is Nx+Ny – 2 = 20+20-2 = 38 with the level of significance at 0.05. it means that guided questions technique can improve the students’ ability in writing descriptive text.